Permeation-Enhanced Degassing Method Based on Xylem Embolism Repair and Gas Permeable Materials - Guo, Lihua (Langmuir : the ACS journal of surfaces and colloids, 2022)
Microfluidic devices have developed a wide range of applications in the fields of biomedicine, chemistry, and analytical science. But it is easy to form and accumulate bubbles in microfluidic devices. These bubbles could decrease the detection sensitivity, cause inaccurate analysis results, and even damage the functional region of the device. Inspired by the embolism repair mechanism of angiosperms and the permeability of gas permeable materials, this work proposes a bioinspired permeation-enhanced degassing method. Bionic redundant pits are used in this method to keep bubbles from spreading between microchannels and maintain the continuity of the flow. A hydrophobic gas permeable material is used to enhance the bubble capture capability and accelerate the degassing process. This method can eliminate bubbles automatically and continuously in real time without auxiliary equipment. Compared to the bubble removal only depending on solution in water, the degassing effect of the permeation-enhanced degassing method shows about 1.6 times improvement in the same conditions, and the capability of trapping bubbles is improved by 1.33 times. In this paper, this method was integrated into a concentration gradient generator and a cell culture device. The results show that the concentration gradient generator with degassing structures can dissolve bubbles in a rapid way and reach the stability of the concentration gradient within 5-15 min. The degassing method can run for a long time and improve the cell density and cell viability of HeLa cells up to 2.64 and 1.12 times, respectively. The method has a broad application prospect in microfluidic fields including biomedical fluid processing, virus detection, and microscale reactor operation